Extensive pericentric rearrangements in the bread wheat (Triticum aestivum L.) genotype "Chinese Spring" revealed from chromosome shotgun sequence data - Ma, Jian; Stiller, Jiri; Wei, Yuming; Zheng, You-Liang; Devos, Katrien M; Doležel, Jaroslav; Liu, Chunji (Genome biology and evolution, 2014)
The bread wheat (Triticum aestivum L.) genotype "Chinese Spring" ("CS") is the reference base in wheat genetics and genomics. Pericentric rearrangements in this genotype were systematically assessed by analyzing homoeoloci for a set of nonredundant genes from Brachypodium distachyon, Triticum urartu, and Aegilops tauschii in the CS chromosome shotgun sequence obtained from individual chromosome arms flow-sorted from CS aneuploid lines. Based on patterns of their homoeologous arm locations, 551 genes indicated the presence of pericentric inversions in at least 10 of the 21 chromosomes. Available data from deletion bin-mapped expressed sequence tags and genetic mapping in wheat indicated that all inversions had breakpoints in the low-recombinant gene-poor pericentromeric regions. The large number of putative intrachromosomal rearrangements suggests the presence of extensive structural differences among the three subgenomes, at least some of which likely occurred during the production of the aneuploid lines of this hexaploid wheat genotype. These differences could have significant implications in wheat genome research where comparative approaches are used such as in ordering and orientating sequence contigs and in gene cloning.
Keywords: chromozomální inverze; pericentromeric regions; genotyp; Chromosome Breakpoints; Chinese Spring; Centromere; chromozomy rostlin; chromozomální delece; chromosomal rearrangement; pšenice; Chromosomes, Plant; centromera; Chromosome Deletion; rekombinace genetická; pericentric inversion; Triticum; Recombination, Genetic; Genotype; translocation; body zlomu chromozomu; Chromosome Inversion; comparative genomics